PENENTUAN PERLAKUAN TERBAIK PENGOLAHAN ABON IKAN GABUS DENGAN MENGGUNAKAN METODE AHP (ANALYTIC HIERARCHY PROCESS) - -, Rahmaniar (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Snakehead fish has many health benefits. However, the consumption level of snakehead fish is still relatively low. One of the product developments that can be made from it is snakehead fish shredded. As a functional food, apart from the nutritional aspect, the acceptance by society should be considered. This research used the AHP (Analytic Hierarchy Process) method to (1) determine the priority criteria aspects in snakehead fish shredded, and (2) establish the best treatment for making snakehead fish shredded. The highest criterion weight was the taste aspect, followed by the colour aspect, fat content, and texture. The best treatment in making snakehead fish shredded based on the criteria was snakehead fish shredded which was processed using a deep frying and spinner and stir-frying with spices Keywords: AHP, shredded, snakehead fish.